Analysis of Sound Myogram of Masseter Muscle in Masticatory Normal Task Movement by a Wavelet Transform Method. - Sato, Iwao; Ueda, Yoko; Kawata, Shinichi; Natsuyama, Yutaro; Yakura, Tomiko; Ueno, Ryuichi; Osada, Takuya; Li, Zhong‐Lian; Miyaso, Hidenobu; Itoh, Masahiro (Journal of Oral Rehabilitation, 2025)
Background: A simple and easy‐to‐use method for recording jaw muscle activity is important for minimising the need for specialised expertise in electrode placement, reducing the burden on the subject. Objective: This study aimed to determine whether masseter muscle activity analysis by sound myography (SMG) combined with laser displacement‐induced skin movement sensing (LDSMS) is comparable to surface electromyography (SEMG). Methods: Eight healthy volunteers (21.0 ± 1.67 years) were included in the study. The measurement tasks consisted of clenching (CL), maximum jaw opening (MJO) and jaw closing and biting (JCB). Masseter muscle activity was recorded simultaneously using SMG, LDSMS and SEMG. We analysed the frequency amplitude spectrum using wavelet analysis and relationships between the signals from the three measurement methods (SMG, LDSMS and SEMG) using principal component analysis (PCA). Results: The masseter muscle activity during jaw tasks analysed using SMG, LDSMS and SEMG was clearly defined. The peak of the integral time–frequency power (ITFP) (mV2/Hz) of the SMG was indicated by approximately CL, 9.8 ± 0.9, JCB, 10.5 ± 1.4 and MJO, 11.3 ± 1.4 Hz. The peaks of the LDSMS (CL, 4.2 ± 0.5, MJO, 4.2 ± 0.5 and JCB, 4.4 ± 0.6 Hz) and SEMG (CL, 54.7 ± 4.6 MJO, 102.1 ± 9.9 and JCB, 71.7 ± 9 Hz) were shown. PCA analysis revealed clusters of masseter muscle activity during jaw tasks obtained by the SMG, SEMG, and LDSMS devices. Conclusion: The SMG with the LMSMS by wavelet analysis is a simple and easy‐to‐use method that can be used to detect jaw muscle activity issues.